Inhibition of glycogen synthase kinase 3β protects liver against ischemia/reperfusion injury by activating 5′ adenosine monophosphate‐activated protein kinase‐mediated autophagy. Issue 4 (21st December 2018) - Kong, Defu; Hua, Xiangwei; Qin, Tian; Zhang, Jianjun; He, Kang; Xia, Qiang
Abstract : Aim: Autophagy has been found to play an important role in hepatic ischemia/reperfusion (I/R) injury. Our previous study has also clarified that rictor deficiency aggravated hepatic I/R injury by suppressing autophagy. Here, we explore whether autophagy participates in glycogen synthase kinase 3β (GSK3β)‐mediated cytoprotection in liver I/R. Methods: Mice were treated with SB216763 to inhibit GSK3β before being subjected to hepatic I/R. Liver injury was evaluated by liver and blood samples. Autophagy was measured by detecting expression of microtubule‐associated protein 1 light chain‐3B (LC3B) II and autophagy protein 5 (ATG‐5), as well as the number of autophagosomes by transmission electron microscope. Primary hepatocytes pretreated with SB216763 for 2 h were subjected to hypoxia/reoxygenation to induce autophagy. The lactate dehydrogenase level was used to evaluate cell death and survival. Autophagy inhibitors and 5′ adenosine monophosphate‐activated protein kinase (AMPK) inhibitor were given in vivo or in vitro . Results: SB216763 significantly increased the number of autophagosomes and the protein levels of LC3B II and ATG‐5 in liver I/R models, which was accompanied by a decline of hepatic necrosis and apoptosis. Consistent with the in vivo study, autophagy and cytoprotection were induced by the inhibition of GSK3β in the in vitro study. Moreover, pretreatment with autophagy inhibitors attenuated the cytoprotective role of autophagy in the GSK3β‐treated liver I/R models. Further analysis showed that pretreatment with an AMPK inhibitor increased mammalian target of rapamycin (mTOR) activity, decreased autophagy, and abrogated GSK3β‐ mediated liver protection. Conclusion: Autophagy was induced by GSK3β inhibition through the AMPK/mTOR pathway and could substantially ameliorate liver I/R injury. Therefore, our findings strongly renew the therapeutic value of the GSK3β/autophagy axis in hepatic I/R injury.